2020
DOI: 10.1371/journal.pone.0228987
|View full text |Cite
|
Sign up to set email alerts
|

What is your definition of Big Data? Researchers’ understanding of the phenomenon of the decade

Abstract: The term Big Data is commonly used to describe a range of different concepts: from the collection and aggregation of vast amounts of data, to a plethora of advanced digital techniques designed to reveal patterns related to human behavior. In spite of its widespread use, the term is still loaded with conceptual vagueness. The aim of this study is to examine the understanding of the meaning of Big Data from the perspectives of researchers in the fields of psychology and sociology in order to examine whether rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 102 publications
(73 citation statements)
references
References 48 publications
0
61
0
2
Order By: Relevance
“…For the purpose of our study we defined Big Data as an overarching umbrella term that designates a set of advanced digital techniques (e.g. data mining, neural networks, deep learning, artificial intelligence, natural language processing, profiling, scoring systems) that are increasingly used in research to analyze large datasets with the aim of revealing patterns, trends and associations about individuals, groups and society in general [ 33 ]. Within this definition we selected participants that conducted heterogeneous Big Data research projects: from internet-based research and social media studies, to aggregate analysis of corporate datasets, to behavioral research using sensing devices.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the purpose of our study we defined Big Data as an overarching umbrella term that designates a set of advanced digital techniques (e.g. data mining, neural networks, deep learning, artificial intelligence, natural language processing, profiling, scoring systems) that are increasingly used in research to analyze large datasets with the aim of revealing patterns, trends and associations about individuals, groups and society in general [ 33 ]. Within this definition we selected participants that conducted heterogeneous Big Data research projects: from internet-based research and social media studies, to aggregate analysis of corporate datasets, to behavioral research using sensing devices.…”
Section: Methodsmentioning
confidence: 99%
“…In our discussion we referred to the contextual dependency of the ethical issues of Big Data and the necessity of a continuous ethical reflection that assesses the specific nuances of the different PLOS ONE types of Big Data in heterogeneous research projects. However we already recognized the risks of conceptualizing Big Data as a broad overarching concept [33]. As a consequence, we believe that future research on Big Data ethics will benefit from a deconstruction of the term into its different constituents in order to provide a more nuanced analysis of the topic.…”
Section: Limitationsmentioning
confidence: 99%
“…Data analysis was carried out using applied thematic analysis (Braun and Clarke, 2006). Detailed information on the study design, sampling and data collection and data analysis can be found elsewhere (Favaretto et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Big Data can be defined as extremely large volumes (in the order of petabytes) of different types of data, available from multiple various sources, which are generated at very high rates of acquisition. 10 Generative Adversarial Networks are trained using the principle of game theory, 9,11 in which the generator learns to efficiently generate new data samples which can only be classified as real images by the discriminator. The use of GANs has paved the way for advanced solutions for a number of computer graphics and computer vision problems and is largely responsible for the recent success in revolutionizing the field of visual computing.…”
Section: Generative Adversarial Networkmentioning
confidence: 99%